Projeto e desenvolvimento de um Retificador Híbrido Trifásico Bidirecional com compensação série no barramento CC em aplicações envolvendo microrredes CC - Costa Neto, Antônio de Oliveira (2023)
This work consists of the experimental development of a topology of a bidirectional threephase hybrid rectifier (BTHR) with voltage series compensation on the DC bus being used under normal operating conditions in a DC microgrid (DC MG), where there is the interconnection of the AC/DC converter with DC MG, participating in the power flow dynamics. In addition, the project also consists of the development and implementation of a new topology that employs digital control using the TMS320F28379D DSP. Due to its potential to provide a high-power factor, low total harmonic interruption in the input currents, in addition to offering a simplified control of voltage regulation in DC buses for the supply of DC loads, subject to variations and voltage disturbances, the topology provides characteristics important for use in DC MG applications, operating as a Bidirectional Grid Interface Converter between the electrical network and the DC bus. The proposed hybrid three-phase rectifier topology has as its main feature an innovative voltage regulation technique called Serious DC Voltage Compensation Technique – (SDCVC). This technique provides a high-power density, since it manages to divide the compression and without complexity the power processing between the passive and active structures of the topology. This series DC compensation technique used is based on the insertion of isolated DC-DC converters with the output capacitor connected in series with the DC bus capacitor provided by a three-phase rectifier not controlled with inductors on the AC side. This new topological arrangement guarantees that the isolated DC-DC converters used to compensate the voltage on the DC bus, process around 30% of the nominal power, guaranteeing, therefore, low power processing in the isolated converters, high efficiency and high-power density. for the uncontrolled rectifier during the rectifying operation. Based on this characteristic, the proposed topology becomes an excellent option in applications involving DC MG.